SiRNA delivered by EGFR-specific scFv sensitizes EGFR-TKI-resistant human lung cancer cells. (January 2016) - Lu, Yuan; Liu, Li; Wang, Yuan; Li, Fakai; Zhang, Jian; Ye, Mingxiang; Zhao, Hu; Zhang, Xiang; Zhang, Mi; Zhao, Jing; Yan, Bo; Yang, Angang; et al.
Abstract: The overexpression of epidermal growth factor receptor (EGFR) is closely associated with a poor outcome in non-small cell lung cancer (NSCLC), and EGFR is an ideal biomarker for the targeted therapy of NSCLC. Although patients with EGFR-activating mutations respond to EGFR tyrosine kinase inhibitors (EGFR-TKIs), they eventually acquire resistance, which typically results from a secondary EGFR mutation or the activation of other signaling pathways. Novel approaches to overcome or prevent EGFR-TKI resistance are clinically important. In this study, we developed an EGFR-scFv-arginine nonamer peptide fusion protein, s-9R, as an siRNA carrier. Here, we show that s-9R effectively and specifically delivers EGFR-siRNAs, KRAS-siRNA and MET-siRNA into NSCLC cells and silences the expression of target genes. The sensitivity of NSCLC cells to gefitinib was restored after treatment with the s-9R/siRNA complex, and the apoptosis rates of the treated cells were significantly higher than those of the control groups. Furthermore, the co-administration of s-9R/siRNA and gefitinib successfully suppressed the progression of H1975 xenograft tumors and extended the life span of tumor-bearing nude mice. Collectively, the results of this study provide not only a new scFv derivative for delivering siRNA into EGFR-overexpressing, TKI-resistant NSCLC cells but also a novel method for overcoming TKI resistance.